고정관념과 불평등: 정체성 선택에 관한 신호이론 - 김영철 (12415, 2012)
We develop an identity choice model within the context of a stereotyping-cum-signaling framework. The model allows us to explore implications of the fact that, when individuals can choose identity, then the distribution of abilities within distinct identi